PENGARUH FASILITAS DAN SOSIAL MEDIA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE OBJEK WISATA GUNUNG DEMPO KOTA PAGAR ALAM - Niken Lestari; Meiffa Herfianti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The decision to visit is a stage carried out by tourists before visiting a tourist attraction. Several factors influence the decision to visit tourists, including facilities and social media. This study aims to determine the effect of facilities and social media on tourists' visiting decisions to the Mount Dempo tourist attraction, Pagar Alam City.This type of research is quantitative research with a descriptive approach. The population of this study were all tourists visiting the Mount Dempo tourist attraction, Pagar Alam City. The number of research samples was 91 people. Data collection was carried out by questionnaires. The data analysis technique uses multiple linear regression analysis techniques.The results of data analysis obtained multiple linear regression equations as follows: Y = 2.354 + 0.352 X1 + 0.369 X2. The results of the analysis show that partially facilities have a positive and significant effect on visiting decisions Â and social media has a positive and significant effect on visiting decisions. Â Simultaneously, there is the influence of facilities and social media on the decision of tourists to visit the Mount Dempo tourist attraction, Pagar Alam City. It I s suggested to the manager of the Mount Dempo tourist attraction, Pagar Alam City, to be able to increase tourist visits to the Mount Dempo tourist attraction, Pagar Alam City by providing the facilities needed by tourists and maximizing social media as a media promotion for the Mount Dempo tourist attraction, Pagar Alam City. Keywords: Visit Decision, Facilities, Social Media